Integration of Maqashid Sharia and Human Development: Case Study in Indonesia - Geraldi Fikri Putra Pradita; Darwanto Darwanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates the connection between Maqashid Syariah principles and the Human Development Index (HDI) across 34 Indonesian provinces from 2019 to 2023. Using panel data regression with a Fixed Effect Model, it examines five Maqashid Syariah dimensions: protection of Din, Nafs, ' Aql, Nasl, and Mal. Results indicate positive and significant impacts on HDI from four dimensions, while protection of intellect shows a negative influence. Together, these dimensions account for 99% of HDI variance. The research suggests policymakers prioritize these areas for sustainable and inclusive human development. Further studies should explore alternative indicators for protecting the intellect dimension to better align with theoretical expectations.